Relation between obesity and health disorders as revealed by the J‐ORBIT clinical information collection system directly linked to electronic medical records (J‐ORBIT 1) - Seiji Nishikage; Yushi Hirota; Yasushi Nakagawa; Masamichi Ishii; Mitsuru Ohsugi; Eiichi Maeda; Kai Yoshimura; Akane Yamamoto; Tomofumi Takayoshi; Takehiro Kato; Daisuke Yabe; Munehide Matsuhisa; et al. (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction Obesity triggers various health disorders, but information on these disorders in real‐world settings remains limited. To address this knowledge gap, we developed a database directly linked to electronic medical records (EMRs). We here present the baseline data for this database, designated Japan Obesity Research Based on electronIc healTh Records (J‐ORBIT). Materials and Methods Individuals with obesity disease diagnosed according to the criteria of the Japan Society for the Study of Obesity were registered in J‐ORBIT from seven medical centers in Japan. We analyzed the relationship between body mass index (BMI), clinical characteristics, and the prevalence of obesity‐related health disorders in this cohort. Results Data were obtained from 1,169 individuals, with a mean (±SD) age of 56.9 ± 15.3 years and a BMI of 31.4 ± 6.1 kg/m2. The prevalence of health disorders varied substantially across BMI categories, with a higher BMI being associated with an increased prevalence of hyperuricemia or gout, obstructive sleep apnea syndrome or obesity hypoventilation syndrome, musculoskeletal disorders, and obesity‐related kidney disease, as well as with a higher frequency of both a family history of obesity and of a history of childhood obesity. Among individuals with a BMI of ≥25 kg/m2, the prevalence of hypertension and dyslipidemia did not increase with BMI, whereas that of glucose intolerance decreased with increasing BMI. Conclusions The J‐ORBIT system, which collects clinical data in real time directly from EMRs, has the potential to provide insight into obesity and its associated health conditions, thereby contributing to improved care of affected individuals.